2022
DOI: 10.1007/s12325-021-02039-4
|View full text |Cite
|
Sign up to set email alerts
|

iStent inject Trabecular Micro-Bypass with or Without Cataract Surgery Yields Sustained 5-Year Glaucoma Control

Abstract: Introduction: This study evaluated the 5-year effectiveness and safety of iStent inject Ò trabecular micro-bypass with or without cataract surgery (Combined or Standalone, respectively) in patients with open-angle glaucoma (OAG). Methods: This prospective longitudinal case series included consecutive iStent inject cases from a single surgeon at a large German academic hospital. Intraocular pressure (IOP), medications, safety, and indicators of disease stability through 5 years were assessed in the Overall coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…17,18 Beyond the pivotal trials evaluating combined procedures for mild to moderate primary OAG, multiple additional studies have shown that implantation of iStent and iStent inject can effectively and safely reduce IOP and medication burden in both combined (with phacoemulsification) and stand-alone (without phacoemulsification) surgery. [20][21][22][23][24][25][26][27][28][29][30][31][32] The evidence also demonstrates an incremental increase in IOP-reducing and medication-reducing effect with a higher number of iStents (1 vs. 2 vs. 3) 20,[33][34][35][36][37][38][39] and suggests a specific incremental benefit of 3 over 2 stents. 16 Subconjunctival bleb-associated surgeries, which bypass the eye's natural drainage system and create a filtering bleb (eg, trabeculectomy, tube shunt implantation, XEN Gel Stent implantation, Preserflo), may be considered when greater IOP lowering is required.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Beyond the pivotal trials evaluating combined procedures for mild to moderate primary OAG, multiple additional studies have shown that implantation of iStent and iStent inject can effectively and safely reduce IOP and medication burden in both combined (with phacoemulsification) and stand-alone (without phacoemulsification) surgery. [20][21][22][23][24][25][26][27][28][29][30][31][32] The evidence also demonstrates an incremental increase in IOP-reducing and medication-reducing effect with a higher number of iStents (1 vs. 2 vs. 3) 20,[33][34][35][36][37][38][39] and suggests a specific incremental benefit of 3 over 2 stents. 16 Subconjunctival bleb-associated surgeries, which bypass the eye's natural drainage system and create a filtering bleb (eg, trabeculectomy, tube shunt implantation, XEN Gel Stent implantation, Preserflo), may be considered when greater IOP lowering is required.…”
mentioning
confidence: 99%
“…Although the follow-up period of 12 months is of relatively short duration, the iStent infinite has the same mechanism of action and treatment approach as the first-generation iStent and second-generation iStent inject devices, which have shown consistent durability in maintaining IOP and medication reductions for up to 8 years postoperative. [16][17][18][20][21][22][23][24][25][26][27][28][29][30][31][32][37][38][39] Hence, long-term studies with iStent infinite would be expected to demonstrate similarly consistent effectiveness and safety over time. No medication washout was done, as this might have placed the enrolled glaucoma patients at undue risk for optic nerve damage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 38 Of note, studies with newer versions of the stents employed in this study, namely XEN 45 and iStent inject, demonstrated significant reduction in visual field loss compared to control. 39 , 40 Moreover, Liu et al demonstrated that the superior hemifield was most affected over a three-year follow-up period in glaucoma patients, although this analysis was after GDD implantation. 20 Our study cohort demonstrated no significant global or regional change in VF metrics over the follow-up period, which indicates a preservation of visual function after MIGS.…”
Section: Discussionmentioning
confidence: 99%
“…The iStent inject W (Glaukos Corporation, Laguna Hills, CA, USA) is a bypass implant between the anterior chamber and Schlemm’s canal to decrease aqueous outflow resistance among MIGS [ 20 , 21 ]. Several studies have suggested the IOP lowering effect of dual iStent inject device implantation in mild-to-moderate open-angle glaucoma [ 22 , 23 , 24 , 25 ]. However, posture-induced IOP changes after the MIGS procedures, including iStent inject W, have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%